An Analysis of the Twitter Account ‘Fufufafa’ Using Kenneth Burke’s Dramatism Theory Among Users Aged 18–22 Years - Agustinawati Silitonga, Amellia Rumanti; Rahadian, Fadli; Hardiansyah, Yudhistira Okta; Jihananda, Jasmine Raisya; Ardiansyah, Eki Putri; Rochman, Hernanda Fahrul Ali (Journal of Media and Digital Society on SDGs, 2025)
his study examines how Kenneth Burke’s Dramatism Theory can help in understanding the narratives built and delivered by Fufufafa’s account on Twitter, especially for users aged 18-22 years. Using a quantitative approach and analysis of Twitter posts, this study found that Fufufafa utilizes elements of dramatism theory to shape its identity, convey messages, and build engagement with its audience. Through this theory, the various actions, motivations, and symbols used by Fufufafa can be read and explored more deeply. The results of this study will show that dramatism is effective for understanding creative communication patterns in social media that are close to the younger generation. Keyword: Dramatism Theory, Kenneth Burke, Fufufafa, Twitter